Analyses of Critical Success Factors and Barriers to the Implementation of Indonesian Mining Safety Management System: Case Study of a Nickel Mine & Processing Company - Guntur Suryaning Hadi; Dyah Santhi Dewi; Ratna Sari Dewi (Jurnal Multidisiplin Madani, 2023)
A very high level of work risk makes the implementation of an occupational health and safety management system imperative, particularly for mining businesses. Because it has an impact on the business's performance, sustainability, and reputation, mining safety is an issue of critical importance. The Republic of Indonesia's government has enacted regulations requiring the Mineral and Coal Mining Safety Management System (SMKP MINERBA) to be applied, as detailed in MEMR Regulation No. 26 of 2018 and its derivatives, through the Ministry of Energy and Mineral Resources (MEMR). The implementation of SMKP MINERBA, however, is still insufficient as shown by the rise in mining accidents that result in harm, lost productivity, and even fatalities. The study came to the conclusion that the existing CSFs could be categorized using the seven factors: SMKP good governance; strong organizational safety culture; organizing and resource availability; Specific - Measurable - Attainable - Relevant - Time Bound (SMART) planning and periodic monitoring; management commitment and strategy; effective Occupational Health & Industrial Hygiene (OH-IH) management; and compliance and safety leadership. In the meantime, the barriers may be classified as follows: low SMKP management commitment, inadequate safety leadership, and poor OHS strategy and execution. Rankings of CSFs and Barriers were also established using the Relative Importance Index (RII), and the ratings might be used by Management to enhance the organization further. As a consequence, the findings of this study and the solutions offered are beneficial to the industry since they may increase practitioners' knowledge and support them in expanding their acceptance in organizations